High-throughput Screening of Photocrosslinking Peptide Libraries for Developing the Method of Site-specific IgG Conjugation - 이병준 (The Graduate School, Ajou University, 2024)
Antibody conjugation's expanded applications in therapeutics and diagnostics have led to the development of various conjugation methods based on chemical or enzymatic reactions. As technology evolves to attach enzymes, toxins, antibody fragments, and small chemical drugs to antibodies, the challenge remains to produce homogeneous antibody conjugate products while preserving their biological activity. The PEptide-DIrected Photo-cross-linking (PEDIP) method was previously developed for site-specific antibody conjugation by using engineered FcIII peptide including photoreactable unnatural amino acid. However, it resulted in decreased binding affinity of the photocrosslinkable peptide toward Fc region due to the introduction of Bpa (photoreactable unnatural amino acid) with bulky functional groups, and antibodies were damaged by UV during the photoreaction process. In this study, I engineered efficiency-enhanced photocrosslinkable peptide toward Fc region via directed evolution approach based on the screening method including bacterial display and Fluorescence-activated cell sorting (FACS), addressing the limitations of PEDIP. This peptide engineering aims to improve the PEDIP method by producing conjugates in a shorter time with less damage of antibodies. The library was designed based FcIII peptide, with the design strategy primarily based on three criteria. First, maintaining the cyclic form of the existing peptide; second, fixing position of pBpa at the most efficient site within the peptide; and finally, ensuring a library size that is feasible for bacterial display. The designed library was expressed using bacterial display, introducing a photosensitive Bpa by unnatural amino acid incorporation system. Expressing cells were subjected to a 365 nm UV irradiation in the presence of antibodies to PEDIP conjugation. Enhanced mutants were selected using Fluorescence-activated cell sorting (FACS). The mutants and antibodies will be utilized to confirm the successful formation of conjugates. Finally, an antibody-drug conjugates (ADCs) with a drug-antibody ratio (DAR) more than 1.9 was produced using drugs and peptide with improved conjugation efficiency. Experimental results using actual cell lines confirmed that the ADCs exhibited toxicity in pM range. Furthermore, it is anticipated that the versatility by using various antibodies and payloads.
학위논문(석사)--분자과학기술학과,2024. 8
Keywords: antibody conjugation; peptide engineering